2013
DOI: 10.2106/jbjs.l.00369
|View full text |Cite
|
Sign up to set email alerts
|

Fractures in Children: Epidemiology and Activity-Specific Fracture Rates

Abstract: The distal part of the radius is the most common fracture site in childhood. Fracture rates differ between various physical activities. The fracture rate for snowboarding was four times higher compared with that for other common childhood sport and recreational activities in our region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
83
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 33 publications
13
83
1
3
Order By: Relevance
“…That said, this study may not apply to places with significantly different climates or where all four seasons are not represented. This study has confirmed that weather and temporal phenomena do indeed affect the workload of the pediatric orthopedic trauma service, which is not surprising considering previous studies have found that over 1/3 of pediatric fractures occur during sport and recreational activity and 71% occur outdoors [3, 13, 14]. However, the results and associations of our study may not be generalizable to other settings due to climate variability, and this is a limitation of this study.…”
Section: Discussionsupporting
confidence: 73%
“…That said, this study may not apply to places with significantly different climates or where all four seasons are not represented. This study has confirmed that weather and temporal phenomena do indeed affect the workload of the pediatric orthopedic trauma service, which is not surprising considering previous studies have found that over 1/3 of pediatric fractures occur during sport and recreational activity and 71% occur outdoors [3, 13, 14]. However, the results and associations of our study may not be generalizable to other settings due to climate variability, and this is a limitation of this study.…”
Section: Discussionsupporting
confidence: 73%
“…to 30% of all fractures in children. 16,17 On the basis of epidemiologic estimates for children younger than 10 years, the incidence of these fractures has been increasing over time, and they are estimated to represent approximately 280 000 ED visits yearly. 1,[17][18][19][20][21][22][23] In With reported rates of redisplacement from 20% to 30% despite anatomic manipulation at presentation, reinforcing remodeling potential alone for these fractures may avoid what is often a temporary reduction and may eliminate the need to closely monitor redisplacement to initial deformity.…”
Section: Discussionmentioning
confidence: 99%
“…In Norway, in a prospective 12-month study of children 0–16 years of age in 2010–2011, Randsborg et al. ( 2013 ) found an overall incidence of distal radius fractures of 560 per 10 5 . The method included evaluation of radiographs and medical charts.…”
Section: Discussionmentioning
confidence: 99%